Islam and “Paganism”: Multilingualism and Multiculturalism in the Kazan Khanate - Khamidullin B.L. (Золотоордынское обозрение)
The aim of the research was to analyze the level of Islamization and, at the same time, cultural and religious tolerance of the multiethnic and multi-confessional Turkic-Finno-Ugric population of the Kazan Khanate. Among the objectives of the research were: to review the degree of development of the state education and enlightenment system in the Khanate; to consider the role of this system in strengthening and improving public relations; and to assess the level of cultural maturity and the so-called “intercultural dialogue” in the country. Research Materials: This included all the information available to the author today from written, archaeological, and folklore sources on the history of the Kazan Khanate, as well as the scientific works of the author himself on the ethnosocial history of the Kazan state published in the last 25 years. Results and Novelty of the Research: The research is a continuation of the author’s systematic research of intercultural tolerance and ethnocultural mixing of the multiethnic and multi-confessional Turkic-Finno-Ugric population of the Kazan Khanate. The article indicates that multilingualism and multiculturalism (introduced into educational and communication spaces at the present stage of social development in the 21st century, in the era of the so-called “post-literacy”), were long successfully implemented in different countries during the Middle Ages, for example in the 15th–16th centuries in the Kazan state. The massive multilingualism and multiculturalism of the khanate’s population was particularly facilitated by the geographical proximity of the Tatar, Mordvin, Chuvash, Bashkir, Mari, and Udmurt’s ancestors living within a single polity, their multifaceted proximity for communication, as well as the rich tradition of Islamic enlightenment and general enlightenment – the presence of a large stratum of educated people, etc. The article concludes that Islam, which penetrated into all spheres of life of the population of the Kazan Khanate, has had a purely positive impact on the development of the country and the people, strengthening intercultural dialogue.